DEVELOPING TEACHING COMPETENCE IN POSTGRADUATES: A PILOT STUDY IN PHYSIOLOGY PRACTICAL TRAINING FOR UNDERGRADUATES - Dr Poonam; Dr Samuel Surjit Singh; Anirudh Tiwari (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
Background It is an established practice, in most medical colleges in the country, that post-graduate [PG] residents of any department teach the practical lessons in the laboratory to the under-graduate [UG] students. However the PG students do not have any formal training in imparting teaching. Aim: To ascertain the benefits of Training the PG students in Teaching Techniques, a pilot study was conducted. Objectives • Comparison of teaching performance of a First year Post Graduate resident before & after training. • Comparison of performance of Under Graduate students taught by the First year PG resident before & after the training • Comparison of performance of UG students taught by the subject after training with the performance of students taught by the Control (conventionally trained second year PG resident). • Self-appraisal by the First year PG resident Results: Observations of our pilot study revealed that training the Post Graduate resident helps not only in improving his performance but also the performance of the end beneficiary- the under graduate students, in under graduate physiology practical classes. It is desirable to make this a part of Post Graduate training in Physiology and other disciplines of Medicine.